Anti-Black violence in twentieth-century Texas - Glasrud, Bruce A.; Dulany, W. Marvin (Texas A&M University Press, 2015)
Introduction: Racism's ugly past; white Texas's twentieth century actions / Bruce A. Glasrud -- Paris is burning: lynching and racial violence in Lamar County, 1890-1920 / Brandon Jett -- An "exciting occurrence": the lynching / Patricia Bernstein -- The Houston riot of 1917 / Calvin Smith -- Violence in a heathen land: the Longview race riot of 1919 / William M. Tuttle Jr . -- A "good job" in the early hours of the morning / Monte Akers -- The Sherman courthouse riot of 1930 / Edward Hake Phillips -- Violence in an "arsenal of democracy": the Beaumont race riot, 1943 / James A. Burran -- Houston and the TSU riot / Bernard Friedberg -- Loyal Garner arrest / Howard Swindle -- The Jasper lynching / Joyce E. King -- Bust town / Nate Blakeslee -- The beating of Billy Ray Johnson / Pamela Colloff -- Afterword: Twenty-first century Texas race relations / Bruce A. Glasrud